Perkembangan Pendidikan Islam di Indonesia Pada Era Reformasi: The Development of Islamic Education in Indonesia in the Era of Reform - Nuri Hafidha Sari, Mei; Hawa, Ewiniarti; Aulia Sari, Febby; Ifendi, Mahfud (CV. Kalimasada Group, 2024)
This study aims to examine the development of Islamic education in Indonesia during the Reform Era, including government policies, the transformation of pesantren and madrasah, and the challenges encountered. A descriptive-qualitative research approach with a literature review method was employed. Data were collected through an analysis of literature, including books, scholarly journals, and policy documents, and were analyzed historically and thematically to describe existing phenomena. The findings reveal that the Reform Era has provided significant opportunities for the development of Islamic education through decentralization and democratization policies. The transformation of pesantren and madrasah stands out as a major success, integrating religious curricula with general knowledge. However, challenges such as regional disparities in quality, issues of radicalism, and the demands of globalization remain obstacles to be addressed. The implications of this study highlight the importance of collaboration among the government, educational institutions, and society to create an inclusive, competitive Islamic education system rooted in the values of moderation.